2022
DOI: 10.3390/ijms23031072
|View full text |Cite
|
Sign up to set email alerts
|

The KRAB Domain of ZNF10 Guides the Identification of Specific Amino Acids That Transform the Ancestral KRAB-A-Related Domain Present in Human PRDM9 into a Canonical Modern KRAB-A Domain

Abstract: Krüppel-associated box (KRAB) zinc finger proteins are a large class of tetrapod transcription factors that usually exert transcriptional repression through recruitment of TRIM28/KAP1. The evolutionary root of modern KRAB domains (mKRAB) can be traced back to an ancestral motif (aKRAB) that occurs even in invertebrates. Here, we first stratified three subgroups of aKRAB sequences from the animal kingdom (PRDM9, SSX and coelacanth KZNF families) and defined ancestral subdomains for KRAB-A and KRAB-B. Using huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
1
3
0
Order By: Relevance
“…Consistent with the models presented, mutation of conserved amino acids within the KRAB‐A domain have previously been shown to abrogate Trim28‐mediated transcriptional repression 7,35,36 . These studies identified and described highly conserved sequence motifs from ZFP10 and ZFP748 that are shared by the KRAB‐ZFP protein family.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Consistent with the models presented, mutation of conserved amino acids within the KRAB‐A domain have previously been shown to abrogate Trim28‐mediated transcriptional repression 7,35,36 . These studies identified and described highly conserved sequence motifs from ZFP10 and ZFP748 that are shared by the KRAB‐ZFP protein family.…”
Section: Discussionsupporting
confidence: 72%
“…Consistent with the models presented, mutation of conserved amino acids within the KRAB-A domain have previously been shown to abrogate Trim28-mediated transcriptional repression. 7,35,36 These studies identified and described highly conserved sequence motifs from ZFP10 and ZFP748 that are shared by the KRAB-ZFP protein family. These sequences, including the "DV," "EEW," and "MLE" motifs, disrupt the interaction with Trim28 and transcriptional repression when mutated (Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…CLAMP is an essential C2H2 Zn-finger protein that binds to thousands of sites in the Drosophila chromosome and is involved in multiple functions, including X chromosome dosage compensation, embryonic reprogramming, and chromatin remodeling, reminiscent of the DPF domain of PHF10, described by Chugunov et al [ 3 ]. Whereas Zn-fingers generally bind DNA, the proteins containing Zn-fingers possess other domain(s) that dictate protein–protein interactions, as also mentioned by Lorenz et al [ 6 ]. Likewise, the CLAMP proteins contain a conserved N-terminal homodimerization domain that facilitates long distance interaction between chromosomal loci.…”
mentioning
confidence: 99%
“…Lorenz et al [ 6 ] drew our attention to eukaryotic transcription factors, specifically a protein-protein interaction domain known as Krüppel-associated box (KRAB), commonly found together with the Cys2His2 (C2H2) Zn-finger domain. This subclass, referred as KRAB Zn-finger (KZNF) proteins, first appeared ~400 million years ago and is widely and abundantly distributed in all extant species from invertebrates to mammals; humans, for example, possess roughly 400 KZNF genes.…”
mentioning
confidence: 99%